PREDIKSI HOME CREDIT DATA ANALISIS PADA PT. XYZ - Annisa’ul Maesaroh; Budi Suyanto (Jurnal Riset Teknik Komputer, 2025)
Data Analytics is one of the fields of the Merdeka Campus Certified Independent Study and Internship Program (MSIB) offered by PT. Nusantara Education Zone (Zenius Education) as a form of Zenius support in building the future of the young generation to develop and improve soft skills and hard skills in the field of Data Analytics for future industrial needs. In the Independent Campus Certified Internship and Independent Study (MSIB) program, students learn basic fundamentals first such as how to think logically well and correctly, draw correct conclusions, make critical reviews, study basic arithmetic and argumentative essays as a basis for learning before entering the field data analytics. In the field of data analytics, students will learn the basics of becoming a data analyst, such as learning the basics of data analytics, the tools used, learning SQL, Python, Pandas, Data Visualization, creating dashboards, learning looker studio and data storytelling. At the end of the lesson, a final project is held in groups as an evaluation of student learning. In this practical work, the final project discusses home credit prediction with the final result being a dashboard that can be used to make decisions.